Student Perceptions on Mata Najwa's Youtube Talk Show in Episode "Pssi Can What Volume 6" (Descriptive Study on Students of Muhammadiyah University of Sidoarjo): Persepsi Mahasiswa pada Tayangan Youtube Talk Show Mata Najwa di Episode “Pssi Bisa Apa Jilid 6” (Study Deskriptif pada Mahasiswa Universitas Muhammadiyah Sidoarjo) - Utama, Handiko Putra; Sinduwiatmo, Kukuh (Journal of Islamic and Muhammadiyah Studies, 2022)
This study aims to describe and find out about the perceptions of Muhammadiyah Sidoarjo university students on the Mata Najwa YouTube talk show in the episode "PSSI can what volume 6". This episode has been watched by the public more than 277 thousand times on youtube. This research uses a qualitative method with a descriptive approach. Data was collected through observation, interviews, and documentation. The data analysis technique used is an interactive model data analysis technique, where the data source comes from interviews with the stages of data collection, reduction, data presentation, and drawing conclusions. The results of this study indicate that the perception of Muhammadiyah Sidoarjo university students on the Mata Najwa YouTube talk show in the episode "PSSI can what volume 6" finds it difficult to trust the authorities on all matters relating to law enforcement, this is due to the lack of strong safety guarantees. to those who reported crimes and the slow handling of PSSI.